Potentials of Jarak Pagar (Jatropha curcas Linn) as Green Belt based on the Rate of its Litter Decomposition - Lailan Syaufina; Nurheni Wijayanto; Istomo Istomo; Khairia Nafia (Jurnal Silvikultur Tropika, 2011)
Previous study found thar Jarak pagar  has potency for fuel break in forest fire control. There are some requirements for vegetation to be fuel break. One of the requirement as fuel break is decomposition race in which the higher decomposition rate may be suitable for fuel break in order to prevent surface fuel accumulation. A study was conducted to analyze decomposition rate of Jarak pagar in the field. Some sample plots were established in forest plantation area of Gunung Hambalang Bogor managed by Perhutani under agroforestry system. The study revealed that Jarak Pagar in the study area has higher decomposition rate when compared to other tree sppecies. Therefore, Jarak Pagar meet the requirement for fuel break from decomposition rate point of view.